2009
DOI: 10.1016/j.nuclphysb.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Lagrangian formulation of massive fermionic totally antisymmetric tensor field theory in space

Abstract: We apply the BRST approach, developed for higher spin field theories, to Lagrangian construction for totally antisymmetric massive fermionic fields in AdS d space. As well as generic higher spin massive theories, the obtained Lagrangian theory is a reducible gauge model containing, besides the basic field, a number of auxiliary (Stückelberg) fields and the order of reducibility grows with the value of the rank of the antisymmetric field. However, unlike the generic higher spin theory, for the special case unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…One should notice that the case of totally antisymmetric spin-tensors developed in Ref. [60] is contained in the general Lagrangian formulation for s 1 = s 2 = ... = s k = 3 2 , k = [(d − 1)/2]. As examples demonstrating the applicability of the general scheme, it is shown that it contains as a particular case the Lagrangian formulation for a mixed-symmetric spin-tensors subject to a Young tableaux with two rows, first developed in [59], as well as the new unconstrained Lagrangian formulation in (6.30)-(6.34) for mixed-symmetry fermionic HS fields with three groups of symmetric indices subject to a Young tableaux with three rows, obtained in the literature for the first time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One should notice that the case of totally antisymmetric spin-tensors developed in Ref. [60] is contained in the general Lagrangian formulation for s 1 = s 2 = ... = s k = 3 2 , k = [(d − 1)/2]. As examples demonstrating the applicability of the general scheme, it is shown that it contains as a particular case the Lagrangian formulation for a mixed-symmetric spin-tensors subject to a Young tableaux with two rows, first developed in [59], as well as the new unconstrained Lagrangian formulation in (6.30)-(6.34) for mixed-symmetry fermionic HS fields with three groups of symmetric indices subject to a Young tableaux with three rows, obtained in the literature for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…There exists another realization of all irreps be means of a different Fock space H as , generated by fermionic oscillators (antisymmetric basis)â m µ m (x),ân + ν n (x) with the anticommutation relations {â m µ m ,â n+ ν n } = −η µ m ν n δ mn , for m, n = 1, ..., n 1 , and one can complete the below procedure, which follows the prescription of[60] for totally antisymmetric spin-tensors for n 1 = n 2 = ... = n k .…”
mentioning
confidence: 99%
“…To derive the unconstrained formulation from the Lagrangian (2.28) we partially fix the gauge invariance as was done in [43][44][45][46][47][48][49][50][51][52] (putting there the curvature to zero, R = 0), except that we will not fix gauge invariance corresponding to the gauge parameter |ε (we remove only the dependence on b…”
Section: Partial Gauge Fixing and Different Lagrangian Formulationsmentioning
confidence: 99%
“…Our main aim is to derive the gauge invariant Lagrangian using the method of BRST construction [43][44][45][46][47][48][49][50][51][52] in the quadratic approximation in the field strength F μν of the external field. This method in fact yields a gauge invariant Lagrangian description for massive higher spin fields in extended Fock space and therefore the Lagrangian will contain, apart from the basic fields, some additional fields, such as Stückelberg fields.…”
Section: Introductionmentioning
confidence: 99%
“…Within the metric-like approach totally antisymmetric fermionic fields were studied in [38] and [39]. The field potential is an antisymmetric spin-tensor φ µ 1 ...µp:α with the gauge transformations of the form…”
Section: One-column Fieldmentioning
confidence: 99%